A self-sustaining serpentinization mega-engine feeds the fougerite nanoengines implicated in the emergence of guided metabolism - Russell, Michael J. (Frontiers in Microbiology, 2023)
The demonstration by Ivan Barnes and colleagues’ that the serpentinization of fresh Alpine-type ultramafic rocks results in the exhalation of hot alkaline fluids is foundational to the submarine alkaline vent theory (AVT) for life’s emergence to its ‘improbable’ thermodynamic state. In AVT such alkaline fluids ≤150°C, bearing H2>CH4>HS– – generated and driven convectively by a serpentinizing exothermic mega-engine operating in the ultramafic crust – exhales into the iron-rich carbonic Hadean ocean to result in hydrothermal precipitate mounds comprising macromolecular ferroferric-carbonate oxyhydroxide and minor sulfide. As the nanocrystalline minerals fougerite/green rust and mackinawite, the minerals compose the spontaneously precipitated inorganic membranes that keep the highly contrasting solutions apart, thereby maintaining redox and pH disequilibria. They do so in the form of fine chimneys and branching, self-ordered and self-healing (but not self-referential) chemical gardens. These disequilibria favor the reduction of CO2 to HCOO– or CO, and the sulfidation of CH4 to CH3SH – these two products reacting to form acetate in a sequence antedating the ‘energy-producing’ acetyl coenzyme-A pathway. Fougerite is a 2D layered mineral in which the hydrous interlayers themselves harbor 2D solutions, in effect constricted to ~1D by preferentially-directed electron hopping/tunneling, and proton Gröthuss bucket brigading when subject to charge. As a redox-driven nanoengine or peristaltic pump, fougerite forces the ordered reduction of nitrate to ammonium, the amination of pyruvate and oxalate to alanine and glycine, and their condensation to short peptides. In turn these peptides have the flexibility to sequester the founding inorganic iron oxyhydroxide, sulfide and pyrophosphate clusters, to produce metal- and phosphate-dosed organic films and cells. As the feed to the hydrothermal mound fails, the only equivalent sustenance on offer to the first autotrophs is the still mildly serpentinizing upper crust beneath. While the conditions here are very much less bountiful, they offer the same feed and disequilibria the survivors are accustomed to. . Indeed, that the anaerobic nitrate-respiring methanotrophic archaea and the deep-branching Acetothermia presently comprise a portion of that microbiome occupying serpentinizing rocks offers circumstantial support for this notion. However, the conclusion is drawn that, absent fougerite there would be no structured channelway to life.